Juridical Analysis Of Criminal Law Enforcement In The Crime Of Organ Trafficking - Ichsanul Basyir; Obbi Robiansyah; Wildan Mahmudi; Agus Dimyati; Rois Harliyanto (Journal Of Social Science (JoSS), 2024)
This study aims to analyze criminal law enforcement related to organ trafficking cases. This research includes examining the conformity between existing legal regulations and practices in the field, identifying obstacles in law enforcement, and evaluating the effectiveness of measures that have been taken to deal with organ trafficking. The research method used is empirical. The results show that the main obstacles in handling this case include recovery and rehabilitation services for victims from health and social aspects that are appropriate to the needs of victims. This research concludes that legal regulations related to Organ Trafficking Crime are still incomplete. In addition, handling victims is not only the responsibility of the Police but also the Government and community institutions. It is suggested that the prevention and handling of Organ Trafficking should be optimized and integrated through synergistic cooperation between the community, Government, and community institutions in combating this crime.